Impaired fatty liver regeneration post-major resection: a mitochondrial problem. - Robinson, Tyler P; Hamidi, Tewfik; Jiang, Yanlin; Jin, Xiaoling; Carvalho, Robson Francisco [UNESP]; Cury, Sarah Santiloni [UNESP]; Correia, Rafael Ribeiro; Baris, Adrian M; Kronbergs, Andris; Zimmers, Teresa A; Koniaris, Leonidas G (Wolters Kluwer, 2025)
Fatty liver disease is associated with a markedly increased risk of liver dysfunction and death after major hepatectomy. We previously demonstrated impaired hepatocyte proliferation, delayed liver regeneration, and increased mortality in post-hepatectomy murine fatty liver. However, the underlying mechanism(s) remains unclear. In this study, we sought to define the mechanisms underlying fatty liver regenerative failure following resection. The hepatic transcriptome was analyzed after 70% or 80% hepatectomy in lean, and diet-induced obese (DIO) mice. A gene array analysis was conducted. Human liver samples with lean and fatty livers were evaluated in a similar manner. Gene ontology (GO) and KEGG pathways were analyzed. Principal component analysis showed striking differences between lean and DIO livers at baseline and following graded hepatectomy, suggesting fundamental underlying differences in DIO livers. At baseline, DIO livers demonstrated an upregulation of mitochondrial-related processes. Post-hepatectomy, however, these processes were downregulated. PPARγ signaling, which activates mitochondrial biogenesis, was significantly downregulated. Essential mitochondrial functions such as citrate cycle, oxidative phosphorylation, and fatty acid degradation were significantly decreased in the DIO liver after resection, demonstrating an inability to accommodate the increased mitochondrial energy demands associated with the regenerative response. Examination of human fatty livers revealed similar changes in baseline mitochondrial function. Using an unbiased analytic approach, fatty liver demonstrates an inability of mitochondrial-related processes to adapt to increased hepatocellular energetic demands following resection. Future therapies to improve post-hepatectomy mitochondrial function should improve post-resection outcomes in fatty liver patients.